The prevalence of elevated-rim polyethylene liner use in primary total hip arthroplasty in the New York State metropolitan area - Behery, Omar A. (Arthroplast Today, 2019)
In existing radiographic studies on primary total hip arthroplasty (THA) examining the spino-pelvic effect on THA instability, there is no control of the type of polyethylene liner used, which may be a significant confounder of the results. We sought to determine the prevalence of the use of elevated liners in primary THA using regional implant company sales data. A total of 12,528 liners were analyzed, demonstrating that the overall regional percentage use of lipped liner use is high and varies inversely with larger head sizes. This prevalence data suggests that it is important to consider the use of lipped liners as a confounding variable that should not be overlooked in radiographic studies analyzing cup position and THA instability.